On the Probability Density of the Nuclei in a Vibrationally Excited Molecule - Schild, Axel (Frontiers in Chemistry, 2019)
For localized and oriented vibrationally excited molecules, the qualitative features of the one-body probability density of the nuclei (one-nucleus density) are investigated. Like the familiar and widely used one-electron density that represents the probability of finding an electron at a given location in space, the one-nucleus density represents the probability of finding a nucleus at a given position in space independent of the location of the other nuclei and independent of their type.In contrast to the electrons, however, the nuclei are comparably localized.Due to this localization of the individual nuclei, the one-nucleus density provides a quantum-mechanical representation of the "chemical picture" of the molecule as an object that can largely be understood in a three-dimensional space, even though its full nuclear probability density is defined on the high-dimensional configuration space of all the nuclei.We study how the nodal structure of the wavefunctions of vibrationally excited states translates to the one-nucleus density. It is found that nodes do not necessarily lead to visible changes in the one-nucleus density:Already for relatively small molecules, only certain vibrational excitations change the one-nucleus density qualitatively compared to the ground state.It turns out that there are simple rules for predicting the shape of the one-nucleus density from the normal mode coordinates.A Python module for the computation of the one-nucleus density is provided at https://gitlab.com/axelschild/mQNMc.